The EXTREMELY INCONVENIENT adventures of BRONTE METTLESTONE - Moriarty, Jaclyn; Canby, Kelly (2024)
Bronte Mettlestone is enjoying tea and cake when a telegram arrives announcing that her parents have been killed by pirates. This doesn't bother her particularly; they ran away when she was a baby and she has been brought up very pleasantly by her Aunt Isabelle and the Butler. Now, however, her parents have left detailed instructions in their will which must be obeyed or terrible things will happen. Bronte is to travel the kingdoms delivering gifts to her ten aunts, including one who specializes in dragon care, a pair who captain a cruise ship and another who is queen of a small kingdom. But as Bronte's escapades with avalanches, water-sprites and pirates become increasingly dangerous, she begins to wonder if there's more to the journey than the simple delivery of treasure...
First published: Crows Nest, NSW : Allen and Unwin, 2017.
Keywords: Voyages and travels -- Juvenile fiction; Aunts -- Juvenile fiction; Gifts -- Juvenile fiction; Secrecy -- Juvenile fiction; Fantasy fiction; Action and adventure fiction